2019
DOI: 10.1038/s41598-019-49644-6
|View full text |Cite
|
Sign up to set email alerts
|

21-Gene Recurrence Score and Adjuvant Chemotherapy Decision for Breast Cancer Patients with Positive Lymph Nodes

Abstract: The 21-gene recurrence score (RS) assay is prognostic and predictive for hormone receptor (HR)+/HER2-/node- breast cancer (BC) patients. However, its clinical value in node + patients hasn’t been elucidated. HR+/HER2-/pN1 patients operated in Comprehensive Breast Health Center, Shanghai Ruijin Hospital from January 2014 to December 2018, with available RS results were retrospectively included. Clinico-pathological characteristics were compared. Adjuvant chemotherapy recommendations pre-/post- RS assay and actu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Regarding the optimized aCTC cut-off, >50% reduction (n = <50% reduction (n = 49) showed a median PFS of 6 (5-10) vs. 3 (3-5) months (p = 0.0085) and a OS of 24 (17-34) vs. 10 (7-16) months (p < 0.0001). Regarding the optimized iCTC+aCTC >66.7% reduction (n = 57) vs. <66.7% reduction (n = 51) showed a median PFS of 6 (5-10) vs. months (p = 0.0063) and a median OS of 24 [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] vs. 10 (7-15) months (p = 0.0025). The impact of the optimized cut-offs on OS and PFS is shown in Figure 3.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the optimized aCTC cut-off, >50% reduction (n = <50% reduction (n = 49) showed a median PFS of 6 (5-10) vs. 3 (3-5) months (p = 0.0085) and a OS of 24 (17-34) vs. 10 (7-16) months (p < 0.0001). Regarding the optimized iCTC+aCTC >66.7% reduction (n = 57) vs. <66.7% reduction (n = 51) showed a median PFS of 6 (5-10) vs. months (p = 0.0063) and a median OS of 24 [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] vs. 10 (7-15) months (p = 0.0025). The impact of the optimized cut-offs on OS and PFS is shown in Figure 3.…”
Section: Resultsmentioning
confidence: 99%
“…Many prognostic factors for MBC have been identified thus far [14,[28][29][30][31][32][33]. In a previous study we could show that a 25% therapy-induced reduction in both the number of aCTCs and iCTCs in the peripheral blood were associated with increased survival and progression-free survival (PFS) in the MBC setting [24].…”
Section: Discussionmentioning
confidence: 99%
“…Over the past two decades, several gene expression signatures by microarray analysis have been developed in effort to predict prognosis and chemotherapy (CT) benefit ( 17 ). Among them, the 21-gene Recurrence Score (RS) assay was most widely applied and evaluated in clinical trials, which can predict both the benefit of adjuvant CT ( 18 ) and prognosis in HR-positive, human epidermal growth factor receptor-2 (HER2)-negative, node-negative patients ( 19 , 20 ). The 2019 National Comprehensive Cancer Network Clinical Practice Guideline ( 21 ) also suggested to spare selective low-risk patients from adjuvant CT, while to apply adjuvant CT in high-risk patients based on RS results according to TAILORx and NSABP B-20 trials ( 22 , 23 ).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have observed the utility of ODX on node positive patients, and this aspect continues to be discussed in literature 37‐43 . Additionally, the West German Study Group Plan B trial and RxPONDER investigate the relevance of ODX scores in clinically intermediate to high‐risk early stage breast cancer patients, including in node positive patients 38,41‐43,45,46 . We have hence included 16 node positive patients in the current study, but have also analyzed the node negative sub‐cohort separately.…”
Section: Discussionmentioning
confidence: 99%
“…[37][38][39][40][41][42][43] Additionally, the West German Study Group Plan B trial and RxPONDER investigate the relevance of ODX scores in clinically intermediate to high-risk early stage breast cancer patients, including in node positive patients. 38,[41][42][43]45,46 We have hence included 16 node positive patients in the current study, but have also analyzed the node negative sub-cohort separately. Also, all the node positive patients in the current cohort were prescribed ODX at least 5 years ago, and thus, we believe the inclusion of node positive patients in the current cohort is clinically relevant and of interest to practicing clinicians.…”
Section: Discussionmentioning
confidence: 99%